Prevalence And Awareness Of Hypertension In A closed Community Of North India Town - Gupta Anmol K; Gupta B.P; Negi P.C; Ahluwalia S.K; Sood Rajesh (Wolters Kluwer Medknow Publications, 1998)
Research question: What is the prevalence and awareness of high blood pressure in a closed community of Shimla Town? Objective : To study the prevalence & awareness of hypertension in a closed community of North India Town. Design : Cross sectional study. Setting: 36 Institutions of Shimla town. Participants: 7630 employees (20-60 years) Study Variables: Age, sex, body mass index, physical activity Statistical Analysis: Standard deviation, chi square test Results: Prevalence of hypertension in closed community was founded to be 33.2%. The level of awareness in hypertensives was 12.32% in less than 35 years of age group; 22.43% in 35-49 years age group and rose to 27.09% in above 50. Only 307 were taking regular treatment.